Rapid detection of Pseudomonas aeruginosa by recombinase polymerase amplification combined with CRISPR-Cas12a biosensing system - Liu, Shuang; Huang, Siyuan; Li, Fang; Sun, Yuanyuan; Fu, Jin; Xiao, Fei; Jia, Nan; Huang, Xiaolan; Sun, Chunrong; Zhou, Juan; Wang, Yi; Qu, Dong (Frontiers in Cellular and Infection Microbiology, 2023)
Pseudomonas aeruginosa (P. aeruginosa) is an important bacterial pathogen involved in a wide range of infections and antimicrobial resistance. Rapid and reliable diagnostic methods are of vital important for early identification, treatment, and stop of P. aeruginosa infections. In this study, we developed a simple, rapid, sensitive, and specific detection platform for P. aeruginosa infection diagnosis. The method integrated recombinase polymerase amplification (RPA) technique with clustered regularly interspaced short palindromic repeat (CRISPR)–CRISPR-associated protein 12a (Cas12a) biosensing system and was termed P. aeruginosa–CRISPR–RPA assay. The P. aeruginosa–CRISPR–RPA assay was subject to optimization of reaction conditions and evaluation of sensitivity, specificity, and clinical feasibility with the serial dilutions of P. aeruginosa genomic DNA, the non–P. aeruginosa strains, and the clinical samples. As a result, the P. aeruginosa–CRISPR–RPA assay was able to complete P. aeruginosa detection within half an hour, including RPA reaction at 42°C for 20 min and CRISPR-Cas12a detection at 37°C for 10 min. The diagnostic method exhibited high sensitivity (60 fg per reaction, 8 copies) and specificity (100%). The results of the clinical samples by P. aeruginosa–CRISPR–RPA assay were consistent to that of the initial result by microfluidic chip method. These data demonstrated that the newly developed P. aeruginosa–CRISPR–RPA assay was reliable for P. aeruginosa detection. In summary, the P. aeruginosa–CRISPR–RPA assay is a promising tool to early and rapid diagnose P. aeruginosa infection and stop its wide spread especially in the hospital settings.